Exoticism in “Harry Potter and The Sorcerer’s Stone” and “Archipelagos: Wizarding School in Nusantara” - Fazrin, Okti Winarti Aulia; Nurholis, Nurholis; Priyawan, Pepen (Universitas Negeri Makassar, 2025)
Abstract. This study contributes to a deeper understanding of how exoticism in fantasy literature is shaped by cultural backgrounds and the use of magical elements. . A comparative qualitative approach is used due to the use of narrative analysis in this study and is necessary to determine the similarities of the study objects. This study analyzes elements such as objects, characters, dialogues or narratives, and rituals or customs collected from both novels as primary data sources. The finding shows the distinct cultural background to build the exoticism. Harry Potter draws extensively from Western and Europe traditions, folklore, myths, and Greek mythology, applying these to create its magical world. In contrast, Archipelagos adopts Asian culture, particularly Indonesian traditions, to enhance the exoticism of its story. The magical elements in this novel are deeply connected to human relationships with nature and animistic beliefs that are central to Indonesian culture. Voldemort and Berong are cultural villain conceptions that have a strong basis in their respective mythologies. The different cultural influences in each novel appear in these differences. The research demonstrates that the cultural context is important in the development of exoticism in fantasy literature Keywords: exoticism, comparative analysis, fantasy, harry potter, magical element, novel